Meta‐analysis of clinical metabolic profiling studies in cancer: challenges and opportunities - Jermaine Goveia; Andreas Pircher; Lena‐Christin Conradi; Joanna Kalucka; Vincenzo Lagani; Mieke Dewerchin; Guy Eelen; Ralph J DeBerardinis; Ian D Wilson; Peter Carmeliet (EMBO Molecular Medicine)
Abstract Cancer cell metabolism has received increasing attention. Despite a boost in the application of clinical metabolic profiling (CMP) in cancer patients, a meta‐analysis has not been performed. The primary goal of this study was to assess whether public accessibility of metabolomics data and identification and reporting of metabolites were sufficient to assess which metabolites were consistently altered in cancer patients. We therefore retrospectively curated data from CMP studies in cancer patients published during 5 recent years and used an established vote‐counting method to perform a semiquantitative meta‐analysis of metabolites in tumor tissue and blood. This analysis confirmed well‐known increases in glycolytic metabolites, but also unveiled unprecedented changes in other metabolites such as ketone bodies and amino acids (histidine, tryptophan). However, this study also highlighted that insufficient public accessibility of metabolomics data, and inadequate metabolite identification and reporting hamper the discovery potential of meta‐analyses of CMP studies, calling for improved standardization of metabolomics studies.